Vocational education students’ perception of entrepreneurship education skills as prognosticators of business start-up at Jigawa State Colleges of Education Gumel - Amar, Haruna Idris; Ibrahim, Rabi’u; Musa, Garba (2020)
The researchers empirically investigated the Vocational education students’ perception of entrepreneurship education skills as prognosticators of business start-up at Jigawa state colleges of education Gumel. In order to investigate this study, the researchers raised two (2) research questions and two (2) hypothesis. Related literature was reviewed and the entrepreneurial event model (EEM) developed by Shapero and Sokol in 1982 was adopted as the conceptual framework for the study. The framework showed at a glance the various stages and processes that eventually climaxed into business formation. The survey design was used in the study. Six hundred and twenty eight (628) vocational education students from Agricultural education, Business education, Fine and Applied Art education, and Home economics education in the college formed the population of the study out of which a sample size of one hundred and fifty seven (157) students were selected using the proportionate stratified random sampling technique. The instrument used for data collection was the questionnaire tittle: Vocational Education Students’ Perception of Entrepreneurship Education Skills Questionnaire (VESPEESQ) and it was divided into two sections – A and B. Section A consists of the demographic information of the respondents while section B consist of thirteen (13) opinion statements structured in a 4-point rating scale. The instrument was validated by experts in the school of secondary education (vocational and technical education programme), Jigawa state college of education, Gumel and the test re-test method of reliability was used in obtaining reliability co-efficient of 0.78. The instrument was administered to the respondents with the help of research assistants and the data collected was subject to statistical analysis. The descriptive and inferential statistical tools were used in analysing the data. The data generated for the study were analyzed using simple percentage, mean and standard deviation to answer the personal data and research questions while the null hypotheses were tested at 0.05 level of significance using t-test with inferential statistic of SPSS version 21. The findings revealed that the respondents have positive perception towards entrepreneurship education. It also revealed that there are challenge plaguing the acquisition of entrepreneurial knowledge and skills such as lack enough practical, lack of adequate facilities etc. Among the recommendations advanced by the researchers was that, there should be conscious efforts by educators to properly transmit the entrepreneurial skills to the learners with ease, practical examples should be included in the lectures, teachers should maintain cordial relationship with students.